The Relationship between Content Used, Time Spent and Cyberbullying on Social Media with Social Skills - Megat Ibrahim, Nan Zakiah; Ibrahim, Mohammad Shamsul (Journal of Techno-Social, 2021)
Based on the past research, there are still limited studies in proving content used on social media, time spent on social media, cyberbullying contributes to the social skills which is deemed unimportant and irrelevant in Malaysia. Therefore, this study is intended to show the variables do have relationship to one another, determining each of the objective in this research is proven to be right. This study applied the Theory of Planned Behaviour as the main theory to fortify and take the relationships at a greater distance between each variable. Quantitative methods were applied in this study and data were collected through the distribution of questionnaires to 181 respondents who were students at Kolej Universiti Poly-Tech MARA pursuing Diploma in Corporate Communication. In addition, the findings showed a significant relationship between content used on social media, time spent on social media, cyberbullying to behaviour and reaction of an individual. Established evidence between variables that are, content used on social media, time spent on social media and cyberbullying is affecting behaviour and reaction of an individual. Hence, this study assisted to the field of communication through the establishment of a more comprehensive variables related to behaviour and reaction of an individual and supported to Planned Behavior Theory.